2015
DOI: 10.1161/circimaging.114.002757
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality by Stress Echocardiography in 2835 Diabetic and 11 305 Nondiabetic Patients

Abstract: Background— To compare the capability by stress echocardiography results to predict overall mortality in a large unselected cohort of diabetic and nondiabetic patients. Methods and Results— The study group comprised 14 140 patients (2835 diabetics and 11 305 nondiabetics) who underwent stress echocardiography for evaluation of known (n=5671) or suspected (n=8469) coronary artery disease. Ischemia at stress echocardiography was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 31 publications
(29 reference statements)
2
19
0
Order By: Relevance
“…Electrocardiographic and hemodynamic changes during stress were not analyzed in our study, but these parameters have never been clearly associated with prognosis during dipyridamole stress echocardiography 7, 8, 9…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiographic and hemodynamic changes during stress were not analyzed in our study, but these parameters have never been clearly associated with prognosis during dipyridamole stress echocardiography 7, 8, 9…”
Section: Discussionmentioning
confidence: 99%
“…It is also widely documented that the ability of SE to identify a low-risk subset is blunted in clinically identifiable subgroups, such as the elderly,19 males,20 diabetics,12 those with left bundle branch block,21 patients with baseline resting left ventricular dysfunction14 or patients undergoing antianginal therapy at the time of testing 22. Other studies have reported that the magnitude of risk associated with SE abnormalities is independent on sex,23 and it is more effective if not only the presence but also the extent of WMAs is considered24 25 also in elderly patients 26.…”
Section: Discussionmentioning
confidence: 99%
“…In our population, 76% of recorded deaths were non-cardiac, whereas in the study by Sicari and coworkers (10), the non-cardiac deaths accounted for 52.1%. Recently, Cortigiani and coworkers (18) reported that inducible ischaemia in SE is correlated to all-cause mortality in a very large cohort of diabetic and non-diabetic patients. They were not able to separate cardiac deaths and hence reported all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%